1996
DOI: 10.1177/074873049601100203
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Behavioral Stimulation from Females Accelerates Recrudescence in Male Syrian Hamsters Exposed to Short Days

Abstract: Interaction with female hamsters maintained under long photoperiods (LP) accelerates behavioral recrudescence in short photoperiod (SP) males. In this experiment, the authors investigated the effects of various types of female sociosexual cues on different measures of reproductive recrudescence in the male. Five groups of SP males were exposed to different female cues for 3 weeks (Weeks 12 to 15). At Week 16, males were allowed to interact with estrus females; behavioral, physiological, and fecundity measures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Evidently some nonphotoperiodic seasonal factor(s) must override the normal photoperiodic input in the wild. Food, water, ambient temperature and social cues have all been shown to alter seasonal traits ( Whitsett & Lawton 1982;Desjardins & Lopez 1983;Eskes 1983;Nelson et al 1983;Pearce & Oldham 1988;Schneider & Wade 1989;Wayne et al 1989;Honrado & Fleming 1996;Hegstrom & Breedlove 1999;Kriegsfeld et al 2000a,b;Larkin et al 2001Larkin et al , 2002Reynolds et al 2003;Schoech et al 2004;Genin et al 2005), including a single plant compound identified in newly grown vegetation that stimulates reproduction in wild montane voles (Microtus montanus) during the winter months (Berger et al 1981).…”
Section: (C) Timers Versus Clocksmentioning
confidence: 99%
“…Evidently some nonphotoperiodic seasonal factor(s) must override the normal photoperiodic input in the wild. Food, water, ambient temperature and social cues have all been shown to alter seasonal traits ( Whitsett & Lawton 1982;Desjardins & Lopez 1983;Eskes 1983;Nelson et al 1983;Pearce & Oldham 1988;Schneider & Wade 1989;Wayne et al 1989;Honrado & Fleming 1996;Hegstrom & Breedlove 1999;Kriegsfeld et al 2000a,b;Larkin et al 2001Larkin et al , 2002Reynolds et al 2003;Schoech et al 2004;Genin et al 2005), including a single plant compound identified in newly grown vegetation that stimulates reproduction in wild montane voles (Microtus montanus) during the winter months (Berger et al 1981).…”
Section: (C) Timers Versus Clocksmentioning
confidence: 99%